A Comprehensive Study of A. Zh. Mashanov’s Islamic Heritage and Its Impact on Historical Scholarship - Shabambayeva, Anara; Dukenbayeva, Zadash; Turlybekova, Aigul; Khassenova, Zhazira; Talgatbek, Manash (Journal of Al-Tamaddun, 2025)
The relevance of the study is determined by the need for multifaceted examination and analysis of the extensive literary legacy of the Kazakh scientist and encyclopaedist Akzhan Mashanov. The purpose of the investigation is to summarise and analyse the historic heritage of Mashanov, and to highlight the main trends of the historical works of the scientist. The study employed both general scientific methods of analysis and synthesis, ascending from the abstract to the concrete and vice versa, notably, the descriptive method, the comparative method, and special methods of historiographical research, in particular, the comparative-historical method, critical analysis, as well as the method of discourse analysis. This study delves into A. Mashanov’s writings concerning the history of science and explores his examinations of the life and contributions of the Islamic scholar Al-Farabi to modern science. The findings reveal that A. Mashanov’s historical heritage is remarkably vast and diverse, extending well beyond the realm of Farabi studies. The theoretical significance of the study lies in broadening the discussion of the historic heritage of A. Mashanov, expanding knowledge about him, as well as further exploring aspects of his creative work and the multifaceted personality of the great scholar. The practical significance of the work lies in a thorough study of A. Mashanov’s scientific findings as an encyclopaedic scholar, which could have an impact on subsequent research in various areas.